A Three-Tier Model for Intertextuality in the Holy Qurᾱn - Sardaraz, Khan; Roslan, Ali; Nusrat, Aasia (Abdul Wali Khan University Mardan, Pakistan, 2020)
In previous literature, intertextuality has been applied to the interpretation of the Holy Qurᾱn, but it lacks a coherent and systematic approach. So far, little or no attempt has been made to propose or design a systematic model of intertextuality for the interpretation of the Holy Qurᾱn. This paper reviews both the modern Western and Islamic theoretical literature on intertextuality. Besides, it exhaustively reviews the intertextual approaches to the interpretation of the Holy Qurᾱn both in classical exegetical tradition and in modern research studies. The findings reveal that the existing approaches are either sketchy and sporadic, or generic or rigid, and cannot account for a comprehensive interpretation of the Holy Qurᾱn. They do not suggest any systematic model for search and selection of intertextual links in the Holy Qurᾱn. The review also shows that the modern theoretical literature on intertextuality in Western tradition misses the theoretical literature on the tool of intertextuality in Islamic discourse. On the basis of its findings, this paper, keeping in view the sensitivity of the religious discourse, suggests a 3-tier model of intertextuality for interpretation of the Holy Qurᾱn, consisting of lexical, topical and grammatical/stylistic intertextual links. This paper also suggests that future research may focus on its application to Qurᾱnic interpretation or/and to frame more vibrant models of intertextuality, drawing on the modern trends in linguistics, to serve the aim of comprehensive interpretation of the Holy Qurᾱn.